Mobile Phones and Climate Information Access Among Smallholders in East Java, Indonesia - Syauqi Agung Firmanda; fatahullah (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: The increasing adoption of mobile phones among smallholder farmers in Indonesia presents new opportunities to access agrometeorological and climate change information, essential for climate adaptation in rural agricultural areas. Aim: This study examines the extent to which mobile phone ownership influences access to climate change adaptation information among smallholder farmers in East Java. Methods: A cross-sectional survey was conducted involving 7,850 smallholder households. The study assessed the relationship between mobile phone ownership and its use for accessing climate-related information, participating in farmer groups, and conducting agricultural transactions. Logistic regression was applied to identify key determinants of mobile phone utilization. Results: Of the total respondents, 54.4% reported owning a mobile phone. Among them, 46.4% used their phones to access climate change information, 41.4% engaged in buying and selling agricultural products, and 46.4% participated in farmer organizations. Mobile phone ownership and group membership were significantly associated with mobile phone use for agricultural purposes (p < 0.001). Conversely, age and household income were not statistically significant. Notable variations were also observed in relation to smartphone ownership, gender, and educational level, with higher education and female participation linked to increased utilization of phones for climate-related activities. Conclusion: Mobile phone ownership plays a critical role in enhancing access to climate adaptation information and agricultural engagement among smallholders. The findings highlight the potential of digital tools to strengthen resilience and support climate-smart practices. Promoting equitable access to mobile technology, particularly for women and less-educated farmers, is vital for inclusive agricultural adaptation strategies.